Molecular characterization of VP4, VP6, VP7, NSP4, and NSP5/6 genes identifies an unusual G3P[10] human rotavirus strain - Pattara Khamrin (2018)
An unusual strain of human rotavirus G3P[10] (CMH079/05) was detected in a stool sample of a 2-year-old child admitted to the hospital with severe diarrhea in Chiang Mai, Thailand. Analysis of the VP7 gene sequence revealed highest identities with unusual human rotavirus G3 strain CMH222 at 98.7% on the nucleotide and 99.6% on the amino acid levels. Phylogenetic analysis of the VP7 sequence confirmed that the CMH079/05 strain formed a cluster with G3 rotavirus reference strains and showed the closest lineage with the CMH222 strain. Analysis of partial VP4 gene of CMH079/05 revealed highest degree of sequence identities with P[10] rotavirus prototype strain 69M at nucleotide and amino acid levels of 92.9% and 94.6%, respectively. Phylogenetic analysis of the VP4 sequence revealed that CMH079/05 and 69M clustered closely together in a monophyletic branch separated from other rotavirus genotypes. To our knowledge, this is a novel G-P combination of G3 and P[10] genotypes. In addition, analyses of VP6, NSP4, and NSP5/6 genes revealed these uncommon genetic characteristics: (i) the VP6 gene differed from the four other known subgroups; (ii) the NSP4 gene was identified as NSP4 genetic group C, an uncommon group in humans; and (iii) the NSP5/6 gene was most closely related with T152, a G12P[9] rotavirus previously isolated in Thailand. The finding of uncommon G3P[10] rotavirus in this pediatric patient provided additional evidence of the genetic diversity of human group A rotaviruses in Chiang Mai, Thailand. © 2008 Wiley-Liss, Inc.